TANTANGAN LITERASI ERA MEDIA DIGITAL (ANALISA PENGGUNA MEDIA BERDASARKAN MODEL KEMUNGKINAN ELABORASI) - Yudha, Reza Praditya (Interaksi: Jurnal Ilmu Komunikasi, 2017)
Abstract                Not only information, social media also encounters negative content and hoax. Not resolved yet, precisely social media is used as reference or source by mass media. In fact, media literacy has been put into practice and exposed the dangers of negative content since long time ago. Two interesting phenomena are; negative content that predicted would be soar on Jakarta Governor Election, April 2017, was missed. Those negative content still exists, organized, even commodified nowdays. The second phenomenon, the community is not just as an audience anymore. They even more daring to exist as an artist in social media. The study aims to analyze the use of media and its implications on media institution. It is important to determine the accuracy of media literacy strategies based on massive, reactive, and plural Indonesian public character.               Research is in the literature review area, analyzing mass communication strategy, and presented by descriptive qualitative. The Elaboration Likelihood Model that explains  central or peripheral routes of public message processing and attribution is used as the theoretical basis. The results; public using central routes are motivated for economic and social benefits. While the aspect of ability of the route is not synergy due to low competence and public ability to be critical. The peripheral route is formed by convenience, wide, and real time interaction in social media. Researcher concludes, literacy requires ethical material and its implications in social life. For example by showing the impact and relevance of media usage in social situations. In addition, public access to seek the truth, provide feedback, and discussions need to be opened wide so that the public can think critically without intervention or doctrine. Keywords : Negative Content, Media Institutions, Elaboration Likelihood Model